Molecular Biological Study of Anti-cancer Effects of Bee Venom Aqua-acupuncture - Park Chan-Yol; Seo Jung-Chul; Choi Do-Young; Ahn Byoung-Choul (Korean Pharmacopuncture Institute, 2000)
To study anti-cancer effect and molecular biological mechanism of bee venom for aqua-acupuncture, the effects of bee venom on cell viability and apoptosis were analyzed using MTT assay, tryphan blue assay, [3H]thymidine release assay, flow cytometric analysis, and activity of caspase-3 protease activity assay. To explore whether anti-cancer effects of bee venom are associated with the transcriptional control of gene expression, quantitative RT-PCR analysis of apoptosis-related genes was performed. The obtained results are summarized as follows: 1. The MTT assay demonstrated that cell viability was decreased by bee venom in a dose-dependant manner. 2. Significant induction of apoptosis was identified using tryphan blue assay, [3H]thymidine release assay, and flow cytometric analysis of sub G1 fraction. 3. In analysis of caspase-3 protease activity, the activity had increased significantly, in a dose-dependant manner. 4. Quantitative RT-PCR analysis of the apoptosis-related genes showed that Bcl-2 and Bcl-XL were down-regulated whereas Bax was up-regulated by bee venom treatment.